Blue Energy Plants and Preservation of Local Natural and Cultural Resources - Andreadou, Tatiana; Kontaxakis, Dimitrios; Iakovou, Konstantina Vasiliki (Frontiers in Energy Research, 2019)
Blue energy technology is one of the most promising and emergent RES sectors developed globally. Many of the pilot and/or fully functioning blue energy plants have been installed in northern European countries. Blue energy plants may have onshore and offshore constructions. Even if RES are highly acceptable by community members in a certain region, the construction of such a plant may rise conflicts. Citizens and local public authorities are usually skeptical about its consequences in local economies, environment, and cityscape. MAESTRALE project's main objective is to transfer available blue energy solutions in the Mediterranean basin by creating a quadruple helix model for their implementation, involving all the actors affected (citizens, scientists, policy makers, local authorities, entrepreneurs etc.). MED area is a region having a unique character and history. Its climate, culture, and landscapes make it a perfect tourist attraction in a global scale. Tourism, in other words, is one of the main pillars of the MED economy and it has to be as less affected as possible in the creation and operation of blue energy plants. This paper aims to seek how BE plants would be successfully incorporated in the existing Mediterranean cityscapes and/or landscapes, focusing mainly in Greek territory.